Peran Teknologi dalam Pengembangan Sistem E-Learning yang Interaktif dan Efektif bagi Pendidikan - Palandi, Esther Hesline; Sriyuliawati, Fovi; Aziz, Asyrofi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This article explores the role of technology in the development of interactive and effective e-learning systems for education. Utilizing a qualitative literature review methodology, the study analyzes various technological advancements and their impact on e-learning environments. The findings indicate that integrating multimedia tools, such as videos, simulations, and interactive quizzes, enhances learner engagement and knowledge retention. Furthermore, the incorporation of Learning Management Systems (LMS) facilitates personalized learning experiences, allowing educators to tailor content to meet diverse student needs. The review also highlights the significance of mobile learning, which provides flexibility and accessibility to learners, enabling education to transcend traditional classroom boundaries. However, challenges such as digital divide, technological literacy, and the need for continuous professional development for educators are identified as critical factors that must be addressed to maximize the effectiveness of e-learning systems. This article concludes by emphasizing the necessity for educational institutions to adopt a strategic approach in integrating technology into their curriculum, ensuring that e-learning systems are not only interactive but also effective in fostering meaningful learning experiences. The insights derived from this literature review contribute to a deeper understanding of the evolving landscape of e-learning and provide a foundation for future research in this domain.